USER GENERATED CONTENT DI MEDIA SOSIAL TIKTOK SEBAGAI STRATEGI PROMOSI BISNIS LELEK AUTO LIGHT - Nurkholis, Muhammad; Mintana, Hans Hermang (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The aim of this research is to find out business promotion strategies using user generated content in a car light custom repair shop, namely Lelek Auto Light. In the research, the concept used is user generated content and also the strategy stages which are carried out through the strategy stage concept. The research method used is descriptive qualitative with interview, observation and documentation data collection methods. The results of this research are that Lelek Auto Light uses 3 promotional strategy stages, namely the planning, implementation and evaluation stages. At the planning stage, problem analysis, audience analysis, formulating communication objectives, determining media channels and planning media production are used. In the implementation stage, namely utilizing TikTok social media and managing user generated content which is done with Lelek Auto Light, producing video content to be used as a reference by users. At the evaluation stage, strategy evaluation is carried out and also evaluation of the results of the strategies that have been used.